Le muralisme des années 1930 et 1940 dans les pays du Río de la Plata - Jacques Poloni-Simard (Nuevo mundo - Mundos Nuevos, 2014)
The article presents four muralist proposals in the countries of the Río of la Plata during the 1930s and 1940s: 1) Ejercicio plástico, realized in 1933 in the house of the press baron Natalio Botana by the Mexican David Alfaro Siqueiros during his stay in Argentina, by means of young argentinian artists; 2) the frescoes of Galerías Pacífico (1945-1946), in Buenos Aires still, conceived by the members of the Taller of Arte Mural (Berni, Spilimbergo, Castagnino, Colmeiro, Urruchua); 3) the murals of the school-museum of la Boca (1936), imagined by Benito Quinquela Martín for the establishment which he had created; 4) those of the medical Martirené house of the Saint Bois hospital of Montevideo, realized in 1944 by Joaquín Torres García and his followers of the Taller Torres García.These works are envisaged in the perspective of a “public art” (frustrated for the first one of them), wich establishes an other relationship with the society. If the Argentinian and Uruguayan artists treated the political theme with other means that the muralism (cf. the “Nuevo Realismo” of Antonio Berni), the representation of the social reality is central in the Quinquela Martín’s work. Finally, the muralism allowed Torres García to spread his "Constructivist Universalism". So, with these four muralist programs analyzed, some of the main questions of the Latin American modernism are approached: the “national art”, the American horizon, the utopia of a "art for all".